Management of Folk Wisdom about Health Care and Herb Utilization of Folk Wisdom Herb Groups - hengsuko, ekasak (Journal of Humanities, Social Sciences, and Arts, 2022)
This study aimed to examine a state of folk wisdom management in health and herbal use of local herbal folk wisdom group. The population consisted of doctor of Thai traditional medicine and pharmacy folk wisdom improvement club at M. 4, Ban Nonsrithong, Muang District, Bueng Kan Province, (2) Phu Tok herbal cultivator and transformation group at M. 6, Ban Khamkhanpatthana, Nasang Subdistrict, Sriwilai District, Bueng Kan Province, and (3) Thai wisdom conservationists group at M. 11, Ban Mai Chaiyaphon, Chaiyaphon subdistrict, Muang District, Bueng Kan Province. The sample included local philosophers of folk wisdom management in health and herbal use of local herbal folk wisdom, group members, health community organization, and other members related to community health care. The sample retrieved by simple random sampling and was selected by purposive sampling. The sample groups were herbal folk wisdom philosophers, folk pharmacists, head of all 3 herbal groups, members of the herbal groups, and inheritors from folk wisdom in health and herbal use. The data was collected by the researchers by using participatory action research and the instrument used in this study was adapted from Suwannee Chaichana which was applied to be consistent and in line with the scope and context of the study. The result explored that the folk wisdom management in health and herbal use of local herbal folk wisdom group was divided into 2 areas: (1) in folk wisdom of herbal diversity management, all 3 groups were continuously conserved and cultivated both in local herbs and nonlocal herbs, however, there were some limited in area. (2) In herbal management process, there were management of both in the use of traditional herbs and herbs transformation products. Keywords: folk wisdom management, health, herbal use, local herbs